Unusual patterns of hybridization involving two alpine Salvia species: Absence of both F1 and backcrossed hybrids - Chang, Yuhang; Zhao, Shengxuan; Xiao, Hanwen; Liu, Detuan; Huang, Yanbo; Wei, Yukun; Ma, Yongpeng (Frontiers in Plant Science, 2022)
Natural hybridization plays an important role in speciation; however, we still know little about the mechanisms underlying the early stages of hybrid speciation. Hybrid zones are commonly dominated by F1s, or backcrosses, which impedes further speciation. In the present study, morphological traits and double digest restriction‐site associated DNA sequencing (ddRAD-seq) data have been used to confirm natural hybridization between Salvia flava and S. castanea, the first case of identification of natural hybridization using combined phenotypic and molecular evidence in the East Asian clade of Salvia. We further examined several reproductive barriers in both pre-zygotic and post-zygotic reproductive stages to clarify the causes and consequences of the hybridization pattern. Our results revealed that reproductive isolation between the two species was strong despite the occurrence of hybridization. Interestingly, we found that most of the hybrids were likely to be F2s. This is a very unusual pattern of hybridization, and has rarely been reported before. The prevalence of geitonogamy within these self-compatible hybrids due to short distance foraging by pollinators might explain the origin of this unusual pattern. F2s can self-breed and develop further, therefore, we might be witnessing the early stages of hybrid speciation. Our study provides a new case for understanding the diversification of plants on the Qinghai-Tibet Plateau.